Redefining sounds, outlining places: Rock, scenes and networks - Moreira, Tânia (2016)
In this chapter we present the results of a research project conducted between2012/20131 which sought to contribute to the sociological thought about musical eventslinked to pop rock, attempting to understand how and to what extent the NUT III Tâmegais able to support a rock scene oscillating between the global and the local. As aperipheral region In the Portuguese context, Tâmega is a region that promotesconditions in which culture and recreational areas take a strong role in the consolidationof young peoples individual identities. The results show us a range of rock music fans,the development of musical projects as well as small events linked to the promotion anddiscussion of this musical genre. However, these same social, economic and culturalconditions of Tâmega end up working as an obstacle to further development of the rockscene: there are more bands, more events, more audiences, but, paradoxically, thisintensity has an almost spontaneous nature, and these musicians, mediators andconsumers continue to mobilize themselves especially in an informal, familiar,amateurish logic, making this scene not only a local but an affective one.